2.EFFECT OF STICK SWEET CHERRY EXTRACTS (PRUNUS (SP)) ON SOME BIOCHEMICAL MARKERS IN ALBINO MICE AND BIOLOGICAL ACTIVITIES IN DIFFERENT TYPES OF BACTERIA (Iraqi Journal of Medical Sciences, 2019)
Background:The sweet cherry (Prunus avium L) has a wide variety of secondary metabolites, which has biochemical and biological activity and used as potential source of a drug. There is no data published on stick cherry extract effect on enzymes activities, kidney function test, inflammatory marker and minerals. As well as on antimicrobial activity of stick cherry extract for inhibition the growth of pathogenic bacteria of different types.Objective: To illustrate the effect of ethanolic stick sweet cherry extract on serum enzyme activities; lactate dehydrogenase (LDH), aspartate transaminase (AST), creatine kinase (CK) and the concentration of urea, uric acid, creatinine, C-reactive protein (CRP) also potassium, calcium in serum of albino mice as well as to investigate antimicrobial activity of the extract to inhibit the growth of different types of pathogenic bacteria.Methods: A total of 28 albino mice were classified into three groups, the first control group (G1) consist of 8 animals treated with 0.2 ml/day distilled water, second group (G2) comprised of 10 animals treated with 30 mg/Kg/day of stick cherry extract, third group (G3) formed of 10 animals treated with 100 mg/Kg/day of extract.Results: There was statistically significant reducing effect in serum enzyme activities of LDH, CK (P?0.001) at 30 and 100 mg/Kg/day, and significant change in serum AST at low and high concentration. There is remarkable change in concentration of urea, uric acid, creatinine and increase in potassium and calcium (P?0.001). The result of antimicrobial activity of stick sweet cherry extracts show inhibition the growth of pathogenic bacteria, different types which involves; (Pseudomonas aeruginosa, Escherishia coli, Staphylococcus aureus, Proteus vulgarweris, Serratiam arcescens). This indicates that the chloroform extract was active against the most pathogenic bacteria at all the concentration used and was more than ethanol extracts.Conclusion: Orally administration of sweet stick cherries extracts to albino mice animals caused a potential difference in different biochemical parameters, enzyme activities, LDH, AST, CK, concentration of urea, uric acid and creatinine, C-reactive protein. Those are risk factors for different diseases, inflammatory, oxidative stress, heart disease. This could be minimized or prevented by polyphenols of cherries stick extract.Keywords: Prunus, Creatine kinase, Sweet cherry, CRP, Potassium, Escherichia coliCitation: Saleem MNMN. Effect of Stick Sweet Cherry Extracts (Prunus (SP)) on some biochemical markers in Albino Mice and Biological Activities in Different Types of Bacteria. Iraqi JMS. 2018; 16(2): 114-124. doi: 10.22578/IJMS.16.2.2
Keywords: Prunus; Creatine kinase; Sweet cherry; CRP; Potassium; Escherichia coli